Which pathway to good ideas? An attention-based view of innovation in social networks - Rhee, Luke; Leonardi, Paul M. (Strategic Management Journal, 2018)
[Research Summary: This study introduces the notion of attention allocation in networks to argue that individuals with different types of network structure produce good ideas via different pathways. Using survey data on communication networks at a software company, we find that people with highly constrained networks generate good ideas by following a logic of interrogation, by which they focus their attention on information from a particular contact. Conversely, individuals with less constrained networks produce good ideas by following a logic of recombination, whereby they divide their attention to information coming from across multiple contacts. The results show that in highly constrained networks, interrogation is a more reliable pathway to good ideas than recombination. We discuss the implications of these findings for behavioral strategy, social networks, and innovation. Managerial Summary: People can develop good ideas when they recombine diverse information inputs shared by non-redundant communication partners that span multiple local clusters. But, in an organization, most individuals are embedded in constrained networks of people who know each other and thus typically receive redundant information from work colleagues. This study suggests that they can innovate via a different pathway: through interrogation. We find that people who focus their attention on information coming from a particular person succeed at generating good ideas because they deeply interrogate local knowledge and develop domain-specific insights.]